SABARI, IHILASI, DAN SYUKURU (MENGUAK NILAI-NILAI KEARIFAN LOKAL DIBALIK PRAKTIK AKUNTANSI KEUNTUNGAN) - MOHAMAD ANWAR THALIB; FEBIOLA JUSUF; RIKA OKTAVIANI PINGA; CINDRI TARIKI (STIE Indonesia Malang, 2023)
This research departs from the problem of the lack of profit accounting studies that raise the values of local wisdom. The purpose of this study is to reveal the values of local wisdom behind the profit accounting practice by meatball traders in Gorontalo. This study uses a qualitative method. The results show that profit accounting practiced by meatball traders in Gorontalo is based on local wisdom values in the form of patience (sabari), sincerity (ihilah), and gratitude (syukuru). These three values are reflected in the actions of traders who are still trying to make halal profits despite a drastic decline in income in the midst of the COVID-19 pandemic, and the decision of traders to set aside part of their profits for charitable activities such as making donations and becoming donors for iftar activities in the holy month of Ramadan.Keywords; accountancy; profit; meatball traders; Gorontalo; qualitative